Clinical spectrum, evolution, and management of autoimmune cytopenias associated with angioimmunoblastic T‐cell lymphoma. (30th May 2019) - Crickx, Etienne; Poullot, Elsa; Moulis, Guillaume; Goulabchand, Radjiv; Fieschi, Claire; Galicier, Lionel; Meignin, Véronique; Coppo, Paul; Delarue, Richard; Casasnovas, Olivier; Roos‐Weil, Damien; de Leval, Laurence; et al.
Abstract: Objective: Angioimmunoblastic T‐cell lymphoma (AITL) is frequently associated with autoimmune cytopenia (AIC). Whether such patients have a particular phenotype and require particular management is unclear. Method: Angioimmunoblastic T‐cell lymphoma patients from the multicentric database of the Lymphoma Study Association presenting with AIC during disease course were included and matched to AITL patients without AIC (1/5 ratio). Results: At diagnosis, AIC patients (n = 28) had more spleen and bone marrow involvement (54% vs 19% and 71% vs 34%, P < 0.001), Epstein‐Barr virus replication (89% vs 39%, P < 0.001), gamma globulin titers (median 23 vs 15 g/L, P = 0.002), and proliferating B cells and plasmablasts in biopsies, as compared to control patients (n = 136). The 28 AIC patients had 41 episodes of AIC, diagnosed concomitantly with AITL in 23 (82%) cases. After a median follow‐up of 24 months (range 3‐155), 10 patients relapsed, all associated with AITL relapse. Conclusion: Our results provide new insight into AIC associated with AITL by highlighting the significant interplay between AITL and B‐cell activation leading to subsequent autoimmunity.